Interface para esqueletizado y suavizado de interferogramas - Penalver-Vidal, D. H.; Romero-Antequera, D. L.; Granados Agustín, F. S. (Revista Mexicana de Física E, 2013)
It is developed a GUI (graphical user interface) in order to provide a fast and easy to use computational tool, which performs smoothing and/or skeletonizing of interferometric images. The code used in the interface is based in smoothing algorithms for interferograms, where the intensity distribution along rows or columns of the image is fitted by means of least squares and using Bessel functions of the first kind as basis functions, allowing the suppression of high frequency noise components. Additionally, the dilation method is used using a Strehl structural element in order to perform skeletonizing of the interferograms.